ANALISIS PEMAHAMAN MAHASISWA TEKNOLOGI INFORMASI TERHADAP KONSEP VEKTOR PADA PEMBELAJARAN ALJABAR LINEAR: Analysis Of Information Technology Students’ Understanding Of Vektor Concepts In Linear Algebra Learning - Zaki, Hamit Sarif; Pratama, Habibi Dwika (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2026)
Linear Algebra, particularly the concept of vectors, is an important foundation for Information Technology (IT) students in various applications in computing and computer graphics. This study aims to understand the extent to which Class A IT students at Bangka Belitung University (UBB) understand the concept of vectors conceptually and interpretively, as many students experience difficulties in connecting mathematical calculations with real-world applications. This study used a descriptive quantitative approach involving 21 respondents (saturated sampling) using a 5-point Likert scale questionnaire analyzed through average scores (means) and percentages. The results show that students' conceptual understanding is high (mean around 3.71). However, their ability to interpret computational results is still in the neutral category (mean around 3.19), indicating a gap between their ability to master formulas and their understanding of applications. The main finding shows that 80.9% of respondents really need a learning approach that focuses on visualization to overcome difficulties in understanding space. Thus, it is concluded that instructors need to change their teaching strategies by emphasizing functional interpretation and integrating visual aids to improve the application understanding of vectors.